2022
DOI: 10.1111/1751-7915.14115
|View full text |Cite
|
Sign up to set email alerts
|

GATA transcription factor WC2 regulates the biosynthesis of astaxanthin in yeast Xanthophyllomyces dendrorhous

Abstract: Astaxanthin is a type of carotenoid widely used as powerful antioxidant and colourant in aquaculture and the poultry industry. Production of astaxanthin by yeast Xanthophyllomyces dendrorhous has attracted increasing attention due to high cell density and low requirements of water and land compared to photoautotrophic algae. Currently, the regulatory mechanisms of astaxanthin synthesis in X. dendrorhous remain obscure. In this study, we obtained a yellow X. dendrorhous mutant by Atmospheric and Room Temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Therefore, there is a need for more strong promoters. Furthermore, previous work has shown that astaxanthin metabolism is induced by oxidative stress and light (Zhang et al 2019;Tropea et al 2013;Stachowiak et al 2013;Schroeder et al 1995;Li et al 2023;Liu et al 2006;Kim et al 2005;Vázquez et al 2001), and Huang et al has discovered a homolog of the white-collar 2 transcription factor in X. dendrorhous (Huang et al 2022), hinting that X. dendrorhous may possess stress and light-inducible promoters. Transcriptomics, and particularly differential gene expression (DGE) analysis, is one way that both strong constitutive and regulated promoters could be identified.…”
Section: Gene Expression Analysis For Part Derivation and Elucidating...mentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, there is a need for more strong promoters. Furthermore, previous work has shown that astaxanthin metabolism is induced by oxidative stress and light (Zhang et al 2019;Tropea et al 2013;Stachowiak et al 2013;Schroeder et al 1995;Li et al 2023;Liu et al 2006;Kim et al 2005;Vázquez et al 2001), and Huang et al has discovered a homolog of the white-collar 2 transcription factor in X. dendrorhous (Huang et al 2022), hinting that X. dendrorhous may possess stress and light-inducible promoters. Transcriptomics, and particularly differential gene expression (DGE) analysis, is one way that both strong constitutive and regulated promoters could be identified.…”
Section: Gene Expression Analysis For Part Derivation and Elucidating...mentioning
confidence: 98%
“…The light response systems in X. dendrorhous are relatively unknown, save white collar (Huang et al 2022). However, systems such as cryptochrome, BLUF-domain, rhodopsin, and photolyase are known in other fungi, including a distantly related basidiomycete Ustilago maydis (Yu & Fischer 2019;Brych et al 2016;Brych et al 2021).…”
Section: Transcriptomics Elucidates X Dendrorhous Photobiologymentioning
confidence: 99%
See 1 more Smart Citation
“…ARTP technology has significantly contributed to the improvement and screening of yeast strains. It has proven effective in producing various yeast mutants with specific traits, such as high-yield yeast [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ], salt-tolerant yeast [ 77 , 78 ], and acid-tolerant yeast [ 79 ], among others ( Table 2 ). Saccharomyces cerevisiae , a well-known yeast species, holds immense importance in industries like winemaking, baking, and brewing, with a historical significance dating back to ancient times [ 80 ].…”
Section: Application Of Artp To Fungimentioning
confidence: 99%
“…Through gene knockout and ARTP mutagenesis, they obtained high-producing tyrosine mutants and conducted genome and transcriptome analysis to reveal the underlying mechanism behind the increased tyrosine production. Similarly, ARTP mutagenesis was used to generate a yellow X. dendrorhous mutant and the GATA transcription factor XdWC2 was identified as crucial in controlling astaxanthin production [ 74 ]. This research laid the foundation for understanding the global regulation of astaxanthin biosynthesis and guiding the development of high-yield astaxanthin-producing strains.…”
Section: Application Of Artp To Fungimentioning
confidence: 99%